Emerging and legacy per-and polyfluoroalkyl substances in the rivers of a typical industrialized province of China: Spatiotemporal variations, mass discharges and ecological risks - Wang, Runmei; Zhang, Jian; Yang, Yuanyuan; Chen, Chang-Er; Zhang, Daochang; Tang, Jianhui (Frontiers in Environmental Science, 2022)
Per- and polyfluoroalkyl substances (PFAS) contamination has drawn considerable attention in the rivers of Shandong, China. However, their seasonal variations have not been well addressed due to the geographic scale. Here, surface waters were collected seasonally at estuaries of 13 major rivers in Shandong to investigate the spatiotemporal variations, mass discharges and ecological risks of PFAS. Two novel perfluoroalkyl ether carboxylic acids, hexafluoropropylene oxide-dimer acid (HFPO-DA) and hexafluoropropylene oxide-trimer acid (HFPO-TA), and 10 legacy PFAS were all detectable and their total concentrations (∑PFAS) ranged largely from 23.3 ng/L to 25.4 μg/L. Elevated levels of all target compounds were found in the Xiaoqing River but Majia and Jiaolai Rivers were also of concern. Perfluorooctanoic acid (PFOA) was dominant in all the rivers. Its concentration in the Xiaoqing River estuary increased 6-fold from 2011 to 2014 and reached a plateau during 2014–2020. The nonsignificant seasonality of the PFAS concentrations in rivers with seasonal flows may indicate their different emission patterns (i.e., higher emission in the wet season and lower emission in the dry season). The ratio of maximum to minimum concentration (Cmax/Cmin) was proposed to characterize the influence of local point sources, with Cmax/Cmin ranging from 10 to 14000. Xiaoqing and Yellow Rivers discharged ~98% of ∑PFAS flux to the sea, which was estimated to be 28.0 t in 2020. This study raises attention to the industrial emission patterns of PFAS. Further investigations with higher time resolution were needed to understand the emission patterns of PFAS in Shandong.